GRAPHIC MODELING AS A GEOGRAPHIC ANALYSIS SYNTHESIS: PROPOSAL FOR THE CITY OF LONDRINA-PR - Cocato, Guilherme Pereira [UNESP] (Univ Federal Fluminense, 2024)
As a methodology with a great synthesis capacity and which provides quick-to-understand visual representations, it is understood that graphic modeling needs greater dissemination in Geography research, teaching and learning spaces. In this sense, this work is proposed as an example of the possibilities of using graphic models constructed from urban spaces geographic analyzes. In this case, the chosen spatial area is the city of Londrina-PR. For the elaboration of models to be possible, it is essential to delve deeper into historical formation contents and the city's spatial structuring dynamics, so that the fundamental structures of its constitution can be identified. With this knowledge, individual and synthetic graphic models can be formulated, using basic visual variables, symbolizing the structures learned. This is considered a powerful geographic and cartographic methodology, uniting theoretical-methodological and empirical discussions in its materialization process. At the same time, it can be operationalized by simple software and digital tools, such as QGIS and research on search-engine websites, which are freely accessible and widespread. Therefore, the results obtained encompass, in an integrated manner, both synthetic cartographic materials - well-based and easy to prepare, with a wide scope for the use of individual creativity and didactic applications - and the production of geographic analyzes capable of involving different cuts and scales, from local to global.
Keywords: Spatial organization; Models; Geography Teaching; Thematic Cartography; GIS